The Meta-violence of Trumpism - Samira Saramo (European Journal of American Studies)
The rise of Donald Trump in United States politics relied on violence. This article examines uses of physical and rhetorical violence in the context of the 2016 U.S. Presidential Election campaign to analyze the emergence of a new social movement: “Trumpism.” Though its meaning and utility are fluid and contested, Trumpism offers a useful lens for viewing a new phase of U.S. pop politics. Defined in terms of populism, strongman politics, and identitarianism, Trumpism employed emotional evocations of violence—fear, threats, hatred, and division—which at times erupted into physical displays of aggression. The article argues that the impact of Trumpism can be understood through the lens of meta-violence, evidenced by extreme emotions, social antagonisms, and international tensions.